The seer and the city : religion, politics, and colonial ideology in ancient Greece - Foster, Margaret (University of California Press, 2018)
Seers featured prominently in ancient Greek culture, but they rarely appear in colonial discourse from the archaic and classical periods. Margaret Foster exposes the ideological motivations behind this discrepancy and reveals how colonial discourse's privileging of the colonial city's founder and his dependence on Delphi, the colonial oracle par excellence, entails a corresponding suppression of the seer